The Role of Zakat, Infaq, and Shadaqah In Shaping Indonesia's Macroeconomic Landscape: A Five-Year Study - Nurfitriani (Jeksyah: Islamic Economics Journal, 2024)
The aim of this research is to analyze the impact of Zakat, Infak, and Shadaqah (ZIS) on the macroeconomy (poverty, unemployment, HDI, Gini ratio, and GDP) in Indonesia and to evaluate the effectiveness of BAZNAS's management of ZIS in reducing poverty and enhancing community welfare. Data from 29 provinces in Indonesia were analyzed using a combination of econometric models, including Fixed Effect Models (FEM) and Random Effect Models (REM), to account for both time-invariant and time-varying factors. The research also employed regression analysis to determine the impact of ZIS on various economic and social variables. The results show that ZIS has a significant impact on various economic and social aspects. ZIS can explain 99.8% of GDP variability, indicating a substantial contribution to economic growth. Additionally, ZIS significantly impacts unemployment (11.6%), poverty (4.3%), and income inequality (96.6%). Finally, ZIS shows a very strong positive impact on the Human Development Index (HDI) with an adjusted R-squared of 98.7%. However, the results also indicate that other factors influence unemployment and poverty, requiring additional approaches to address these issues. Overall, ZIS can be an effective strategy for improving community welfare and reducing social inequality.